Sharing too much : musings from an unlikely life [large type] - Evans, Richard Paul (Thorndike Press large print top shelf., 2024)
"Before he was the #1 New York Times bestselling author of holiday classics such as The Christmas Box, Richard Paul Evans was a young boy being raised by a suicidal mother and dealing with relentless bullying. He could not fathom what the future held for him. Now, in this intimate and heartfelt collection of personal essays, Evans shares his moving journey from childhood to beloved author, offering the insightful lessons he's learned and engaging advice about everything from marriage to parenthood and even facing near-death experiences. This is a charming essay collection that is the perfect gift all year round."--